Conceptual Tripod of Ecotourism for Compliance Assessment of a National Park in the Brazilian Amazon - Margarita María Dueñas Orozco; Frederico Yuri Hanai; Heros Augusto Santos Lobo (Journal of Tourismology)
National Parks in Brazil are Natural Protected Areas where ecotourism can be developed associated with nature conservation, respecting the guidelines of its Management Plan (MP). This study comprehensively analyzes the ecotourism compliance of the MP of a National Park located in the Western Amazon region. Qualitative criteria for analysis were developed based on the concept of the International Ecotourism Society, supported by scientific literature. The criteria were used to analyse the Management Plan of the park and to verify its applicability as an analytical tool. The results showed that the plan complied with 53.3% of the criteria and partially complied with 13.3%. The findings of this study point to the great potential of the PNNP for ecotourism, given its rich natural and cultural diversity, which comes from the transition ecotone between important Brazilian biomes and the indigenous populations that inhabit the region.